2018
DOI: 10.3390/nu10070944
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating Pregnancy Weight Gain—What Works and Why: A Systematic Review and Meta-Analysis

Abstract: Excessive maternal gestational weight gain (GWG) contributes to generational obesity. Our aim was to explore efficacy and intervention characteristics (trimester, duration, frequency, intensity, and delivery method) of interventions to prevent excessive GWG. CINAHL, Cochrane, EMBASE, LILACS, MEDLINE, PsycINFO, and Scopus were searched up to May 2018 (no date or language restrictions). Keywords and MeSH terms for diet, GWG, intervention, lifestyle, maternal, physical activity, and pregnancy were used to locate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 150 publications
4
49
0
6
Order By: Relevance
“…103 Study characteristics and methodological quality have been reported previously. 22 For individual results reported in this review, see Tables 1-5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…103 Study characteristics and methodological quality have been reported previously. 22 For individual results reported in this review, see Tables 1-5.…”
Section: Resultsmentioning
confidence: 99%
“…10 In contrast, inadequate GWG The details of the inclusion exclusion criteria have been previously outlined. 22 Briefly, studies were eligible if they were randomized controlled trials, conducted in humans with a primary or secondary aim to reduce excessive GWG. Studies that aimed to encourage GWG were excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence synthesis has shown that antenatal diet and physical activity lifestyle interventions for women have been successful in limiting excessive gestational weight gain [12,13]. However, the effect of lifestyle interventions on reducing adverse maternal events has been difficult to measure at an individual trial level due to sample size limitations and insufficient power.…”
Section: Introductionmentioning
confidence: 99%
“…Excess weight gain during pregnancy is associated with numerous complications, e.g. gestational diabetes, arterial hypertension [19,23,28], and fetal macrosomia [14,29,34]. Currently, it is believed that excess neonatal weight intensifies the problem of obesity both, in childhood and later in life [3-5, 10, 14].…”
Section: Introductionmentioning
confidence: 99%